2016
DOI: 10.25009/cpue.v0i23.2172
|View full text |Cite
|
Sign up to set email alerts
|

Discapacidad y educación superior: ¿Una cuestión de derechos o buenas voluntades?

Abstract: El presente trabajo aborda la relación entre discapacidad, educación superior y derechos humanos. Parte de una investigación sobre la inclusión de estudiantes con discapacidad en la Universidad Veracruzana, la cual tuvo como objetivo principal analizar la representación social de la comunidad universitaria sobre las personas con discapacidad y su inclusión a la universidad. Se presentan los resultados de la aplicación de una encuesta cuyo propósito fue indagar sobre las representaciones sociales de la comunida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
13

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 0 publications
1
3
0
13
Order By: Relevance
“…There are also reports of people with disabilities in urban settings in Colombia, spending more financial resources on taxis than their peers without disabilities due to the lack of accessible buses [42]. More broadly, our results also align with evidence from other contexts in Latin America where students with disabilities identified that the infrastructure to get to and at the university and attitudes of professors and administrative staff pose difficulties for the full enjoyment of the university and to exercise their right to education [41,[43][44][45]. In high income settings, such as the US and Denmark, barriers at the community level prevail where people with disabilities report difficulties in using health care facilities and green spaces, respectively [46,47].…”
Section: Discussionsupporting
confidence: 85%
“…There are also reports of people with disabilities in urban settings in Colombia, spending more financial resources on taxis than their peers without disabilities due to the lack of accessible buses [42]. More broadly, our results also align with evidence from other contexts in Latin America where students with disabilities identified that the infrastructure to get to and at the university and attitudes of professors and administrative staff pose difficulties for the full enjoyment of the university and to exercise their right to education [41,[43][44][45]. In high income settings, such as the US and Denmark, barriers at the community level prevail where people with disabilities report difficulties in using health care facilities and green spaces, respectively [46,47].…”
Section: Discussionsupporting
confidence: 85%
“…La temática de discapacidad actualmente continúa analizándose desde el paradigma médico-rehabilitador-asistencialista, lo que provoca estigmatización hacia este colectivo (Cruz-Vadillo, 2016). La discapacidad en la universidad es vista bajo perspectivas funcionales y limitaciones a los que se encuentran en dicha situación (Figuera y Coiduras, 2013).…”
Section: Tipos De Discapacidades Y Carreras Que Cursan Los Participunclassified
“…Se deben generar espacios educativos libres de exclusión y discriminación. Además, es vital crear estrategias institucionales desde una visión de derechos humanos que tomen en cuenta a este y otros colectivos en condición de vulnerabilidad (Cruz-Vadillo, 2016).…”
Section: Los Desafíos Para Generar La Inclusión Educativa En Los Estaunclassified
See 1 more Smart Citation
“…(43)(44). The government must have a leading role taking the measures as mandated by Article 8 in the CRPD on awareness-raising: "To combat stereotypes, prejudices and harmful practices relating to people with disabilities, including those based on sex and age, in all areas of life"(3).…”
mentioning
confidence: 99%